(untitled) (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2026)
To systematize the analysis of crystal structure, physicochemical properties, electrical conductivity mechanisms, and technological applications of semiconductor materials. Comparative analysis was conducted based on solid-state physics, band theory, synthesis of experimental data, and computational modeling (DFT, Drude–Sommerfeld approach). Quantitative evaluation of band gap energies (Si: 1.12 eV, Ge: 0.66 eV), charge carrier mobility, temperature-dependent conductivity, and doping effects for Si, Ge, and compound semiconductors (GaAs, SiC, GaN) was performed. A precise understanding of physicochemical parameters is critical for enhancing semiconductor device performance and advancing wide-bandgap materials and nanotechnologies.